2014
DOI: 10.1590/s0104-12902014000400025
|View full text |Cite
|
Sign up to set email alerts
|

Segurança do paciente no uso de medicamentos após a alta hospitalar: estudo exploratório1

Abstract: Few Brazilian studies have focused on patient safety strategies for safe use of medications after discharge leading to limited knowledge of current safety practices developed in Brazilian hospitals. The present study aimed to understand the dynamics and challenges of care provided to patients by hospital providers focusing on safe use of medications after discharge. An exploratory study was conducted and data was collected through interviews with physicians, nurses, pharmacists and social workers at the Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
12

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
0
18
0
12
Order By: Relevance
“…Five studies were found related to discharge planning (17)(18)(19)(24)(25) . Planning was centered on the health conditions of patients (19) , cognitive capacity (17,19) , social support, and the needs of patients (19) .…”
Section: Discharge Planning (Dp)mentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were found related to discharge planning (17)(18)(19)(24)(25) . Planning was centered on the health conditions of patients (19) , cognitive capacity (17,19) , social support, and the needs of patients (19) .…”
Section: Discharge Planning (Dp)mentioning
confidence: 99%
“…Planning was centered on the health conditions of patients (19) , cognitive capacity (17,19) , social support, and the needs of patients (19) . Care plans included drug lists and instructions (18,(24)(25) , social support to access health care services (19) , underlying illnesses, warning signs and symptoms, nutritional care, instructions regarding continued use of medications, and clinical follow-ups (18,25) . One study developed a discharge planning guide around safe medication usage for pediatric patients and their caregivers due to their complex health needs (24) .…”
Section: Discharge Planning (Dp)mentioning
confidence: 99%
See 3 more Smart Citations